2004
DOI: 10.1007/s10336-004-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in farming of subalpine meadows on a grassland bird, the whinchat (Saxicola rubetra)

Abstract: The increasing intensity of farming of meadows is supposed to be the major cause for strong declines of many meadow breeding birds. The whinchat, Saxicola rubetra, a Palaearctic migratory bird, is an indicator species of open grassland farmed at a low intensity. Originally widespread throughout Switzerland, it is now restricted to mountain and subalpine grassland. We document the changes in meadow cultivation in subalpine farmland from 1988 to 2002, and the breeding performance and density of the whinchat. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 30 publications
(29 reference statements)
4
102
0
1
Order By: Relevance
“…However, further studies investigating breeding success are needed to rule out that the association with mown areas did not arise as a consequence of maladaptive habitat selection (e.g. Chamberlain & Crick 1999;Müller et al 2005;Gilroy et al 2011;Broyer et al 2012). Important management indications emerge from our findings.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, further studies investigating breeding success are needed to rule out that the association with mown areas did not arise as a consequence of maladaptive habitat selection (e.g. Chamberlain & Crick 1999;Müller et al 2005;Gilroy et al 2011;Broyer et al 2012). Important management indications emerge from our findings.…”
Section: Discussionmentioning
confidence: 71%
“…Such measures could provide financial support to small farms with free-ranging livestock (the so-called "alpeggio" system). However, this may not be sufficient, since grassland species require unmown grassland patches until the end of the breeding season, and mowing should be postponed as much as possible to enhance breeding success and improve suitability of managed grasslands (Müller et al 2005;Brambilla & Pedrini 2011). Financial subsidies for the maintenance of the "alpeggio" system are already provided in the Lombardy Region within the framework of the Rural Development Plan (Allegato I, Decreto n. 970, issued on 13 February 2012, in Italian).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further south, in southern France, Whinchat breeding success was poor at occupied sites below about 1200 m asl, which was considered the approximate upper limit of the negative influence of intensive farming on breeding success by birds in meadows (Broyer 2009). In the Swiss Alps, Whinchats were breeding successfully at about 1500 m asl, within extensively managed meadows with a generally south-facing aspect (Müller et al 2005).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Whinchats Saxicola rubetra are an example of one species that was formerly widespread across European lowlands where it was considered to be a bird typical of semi-natural grasslands and meadows. In many areas it is now confined to upland meadows, where grass cutting dates have not advanced as a result of agricultural intensification (Müller et al 2005, Bolliger et al 2007, Broyer 2009), and also abandoned or derelict agricultural land provides extensive areas of uncut grassland (Frankiewicz 2008, Orowski 2010. Increased nest losses and greater mortality of incubating females attributable to the earlier cutting of meadows (Gruebler et al 2008) and reduced food availability (Britschgi et al 2006) have been identified as causal mechanisms produced by agricultural intensification that have lead to population declines and range contractions of Whinchats.…”
mentioning
confidence: 99%